Development of a Customized Interbody Fusion Device for Treatment of Canine Disc-Associated Cervical Spondylomyelopathy - Joffe, Michelle R.; Parr, William C. H.; Tan, Christopher; Walsh, William R.; Brunel, Laurencie (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objectives The main purpose of this study was to design, manufacture and implant a customized three-dimensional (3D) printed, intervertebral spacer to treat disc-associated cervical spondylomyelopathy (DACSM) in dogs. This study also used advanced imaging to assess implant movement, subsidence and interbody fusion.Animals Two client-owned dogs with DACSM.Method Customized interbody devices were designed and 3D printed in titanium alloy. The devices were implanted in dogs diagnosed with DACSM. The dogs were evaluated at time points 0, 2 and 6 months to determine clinical outcome, degree of interbody fusion, implant migration and subsidence.Results Progressive fusion was noted across the affected intervertebral space by 6 months. Implants mildly shifted cranially in the 2-month interim. There was no subsidence of the intervertebral device through the vertebral end plates in dog 1 and minimal in dog 2 (∼0.5 mm). Clinically, the neurological status improved in both dogs.Conclusions The customized interbody devices restored the intervertebral space and resulted in a degree of interbody fusion and resolution of clinical signs.Clinical Significance This report illustrates preliminary outcomes of DACSM treated with a customized, end plate conforming, intervertebral device. Collaboration between clinicians and engineers with advanced manufacturing technologies can provide a cutting-edge standard of care for patients suffering from DACSM.
Keywords: three-dimensional printing; cervical spondylomyelopathy; customized interbody fusion device; canine; dog